Irregular Warfare: Policy and Practice from 1941-2012 - Hein, Erich (My University, 2012)
Irregular warfare is defined as warfare in which one or more combatants are irregular military rather than regular forces. Irregular forces do not follow the normal pattern of war and think outside the box to defeat their enemies. Another name for irregular warfare is guerilla warfare. In today's modern battlefield irregular warfare is becoming more prevalent among the United States military and its forces. This paper will look at the changes in warfare as well as the policy behind irregular warfare from its beginning in World War Two, to the battlefields in Afghanistan and the Middle East.
Keywords: Irregular warfare--United States--History--20th century; Irregular warfare--United States--History--21st century; Guerilla warfare--United States--History--20th century; Guerilla warfare--United States--History--21st century